Granulomatous response to Coxiella burnetii, the agent of Q fever: the lessons from gene expression analysis - Faugaret, Delphine; Ben Amara, Amira; Alingrin, Julie; Daumas, Aurélie; Delaby, Amélie; Lépolard, Catherine; Raoult, Didier; Textoris, Julien; Mège, Jean-Louis (Frontiers in Cellular and Infection Microbiology, 2014)
The formation of granulomas is associated with the resolution of Q fever, a zoonosis due to Coxiella burnetii; however the molecular mechanisms of granuloma formation remain poorly understood. We generated human granulomas with peripheral blood mononuclear cells and beads coated with C. burnetii, using BCG extracts as controls. A microarray analysis showed dramatic changes in gene expression in granuloma cells of which more than 50% were commonly modulated genes in response to C. burnetii and BCG. They included M1-related genes and genes related to chemotaxis. The inhibition of the chemokines, CCL2 and CCL5, directly interfered with granuloma formation. C. burnetii granulomas also expressed a specific transcriptional profile that was essentially enriched in genes associated with type I interferon response. Our results showed that granuloma formation is associated with a core of transcriptional response based on inflammatory genes. The specific granulomatous response to C. burnetii is characterized by the activation of type I interferon pathway.